2008
DOI: 10.1007/s10508-008-9408-z
|View full text |Cite
|
Sign up to set email alerts
|

Body Size at Birth and Same-Sex Marriage in Young Adulthood

Abstract: An unexplained excess of overweight has been reported among lesbians. In contrast, reports suggest that gay men may be, on average, slightly lighter and shorter than heterosexual men. We studied associations between weight, length, and body mass index (BMI) at birth and same-sex marriage in young adulthood among 818,671 Danes. We used linear regression to calculate differences in mean body measures at birth and Poisson regression analysis to calculate confounder-adjusted incidence rate ratios (IRR) of same-sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…These observations, especially those associating hyperthyroidisms with homosexuality in men, seem to support the prenatal androgen model linking same‐sex attraction in men to under exposure to prenatal androgens, and in women, to overexposure. This model also seems to align with reports of lower body weights and heights on average among homosexual men and higher average body measurements among homosexual women, both at birth and in adulthood …”
Section: Introductionsupporting
confidence: 85%
“…These observations, especially those associating hyperthyroidisms with homosexuality in men, seem to support the prenatal androgen model linking same‐sex attraction in men to under exposure to prenatal androgens, and in women, to overexposure. This model also seems to align with reports of lower body weights and heights on average among homosexual men and higher average body measurements among homosexual women, both at birth and in adulthood …”
Section: Introductionsupporting
confidence: 85%
“…One study found that men who entered same-sex marriages showed lower body size at birth compared to other men (Frisch & Zdravkovic, 2010), but this study did not examine body size at birth in relation to birth order. One study found that men who entered same-sex marriages showed lower body size at birth compared to other men (Frisch & Zdravkovic, 2010), but this study did not examine body size at birth in relation to birth order.…”
Section: Introductionmentioning
confidence: 88%
“…Several studies have considered birth weight in relation to sexual orientation. One study found that men who entered same-sex marriages showed lower body size at birth compared to other men (Frisch & Zdravkovic, 2010), but this study did not examine body size at birth in relation to birth order. Consistent with the hypothesis that fraternal birth order-induced maternal immune responses are associated with homosexuality in males, homosexual men who had one or more older brothers exhibited lower birth weight (Blanchard & Ellis, 2001).…”
Section: Introductionmentioning
confidence: 88%
“…In a U.S. national sample of young people, lesbian and bisexual women as compared with heterosexual women were heavier, and the difference was apparent in adolescence (Austin et al, 2009). A Danish study, however, did not support the hypothesis of weight differences in puberty because women who married women were heavier at birth than women who married men, suggesting that the weight disparity was possibly attributed to prenatal rather than pubertal hormones (Frisch & Zdravkovic, 2010). The remaining and prevalent studies have no bearing on the hypothesis because they focus on sexual-orientation disparities in adulthood and not on BMI differences during adolescence (i.e., puberty).…”
Section: Implications For Sexual Orientation Of Prenatal Hormonal Eff...mentioning
confidence: 85%
“…Homosexual men are shorter than heterosexual men (Bogaert, 2010). The hormonal effect may occur prenatally, at least for some men, rather than during puberty, however, because the Danish study found that men who married men were more likely than men who married women to be shorter in length at birth (Frisch & Zdravkovic, 2010).…”
Section: Implications For Sexual Orientation Of Prenatal Hormonal Eff...mentioning
confidence: 91%